Rain water harvesting for enhancing crop water productivity: an assessment for rainfed areas of India. [Abstract only]. - Sharma, Bharat R.; Rao, K.V.; Vittal, K.P.R. (2008)
Rainfed agriculture generates about 65-70% of the world's staple foods, but rainfed areas in South Asia and Africa, home to the world's largest proportion of drought prone areas (about 44%), have extremely low yield levels. India ranks first among the rainfed agricultural countries of the world in terms of both extent (86 M ha) and value of produce. Due to low land and labour productivity poverty is concentrated in rainfed regions. The large yield gap between the attainable and potential yield shows that a large potential of rainfed agriculture remains to be tapped. Besides several other factors related to agriculture sector as a whole, adverse meteorological conditions in long dry spells and droughts, unseasonal rains and extended moisture stress periods with no mechanisms for storing and conserving the surplus rain to tide over the scarcity/ deficit periods were the major cause for non-remunerative yields and the associated distress. As such productivity of water is very low in rainfed agriculture. Supplementary irrigation is a key strategy, so far underutilised, to unlock rainfed yield potentials and improving crop water productivity in rainfed areas. Since irrigation water productivity is much higher when used conjunctively with rainwater (supplemental), it is logical that under limited water resources priority in water allocation may be given to supplementary irrigation. Therefore an assessment was made under an IWMI-CRIDA study to identify opportunities at the national level for India for water harvesting and supplemental irrigation to overcome dry spells during mid/ terminal droughts so as to stabilize the production. The study identified the dominant rainfed districts for different crops (contributing upto 85% of total rainfed production), made an assessment of the surplus/ runoff available for water harvesting and supplementary irrigation in the identified districts, estimated the regional water use efficiency and effect of supplemental irrigation on increase in production of different crops and finally a preliminary estimate of the economics of water harvesting for supplemental irrigation in rainfed areas. The study identified about 27.5 M ha of potential rainfed area, which accounted for most of the rainfed production and generated sufficient runoff (114 BCM) for harvesting and reutilization. It was possible to raise the rainfed production by 50% over this entire area through application of one supplementary irrigation (28 BCM) and some follow up on the improved practices. Extensive area coverage rather than intensive irrigation need to be followed in regions with higher than 750 mm/ annum rainfall, since there is a larger possibility of alleviating the in-season drought spells and ensure second crop with limited water application. This component may be made an integral component of the ongoing and new development schemes in the identified rural districts. The proposed strategy is environmentally benign, equitable, poverty-targeted and financially attractive to realize the untapped potential of rainfed agriculture in India.